Weingarten surfaces in three-dimensional product geometries - Vitti, Mannaim Gennaro (Universidade Federal de São Carlos, 2025)
In this work, we seek to obtain information about certain types of Weingarten surfaces, approaching this problem through nonlinear partial differential equations. We study particular cases of translation surfaces in the product spaces H2xR and H3 and Helical surfaces in S2xR that verify the property of being a Weingarten Surface. In addition, we also investigate translation surfaces in the Euclidean space E3 that are particular cases of Weingarten Flow Solitons.
Superfícies de Weingarten em geometrias produto tridimensionais
Keywords: Superfícies de Weingarten; Geometrias produto; Fluxo de Weingarten; Sólitons; Equações diferenciais parciais não lineares; Método de Fourier; Separação de variáveis; Equação do calor; Weingarten surfaces; Product geometries; Weingarten flow; Solitons; Nonlinear partial differential equations; Fourier method; Separation of variables; Heat equation; CIENCIAS EXATAS E DA TERRA::MATEMATICA::GEOMETRIA E TOPOLOGIA::GEOMETRIA DIFERENCIAL; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ANALISE::EQUACOES DIFERENCIAIS PARCIAIS; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ANALISE::EQUACOES DIFERENCIAIS ORDINARIAS